Prototipe Sistem Smart Box untuk Keamanan Penerimaan Paket Online Shopping - Valupi, Christine; Ariyadi, Tamsir; Paramyta, Nina; Purwanto, Timur Dali (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to design a tool with a smart box system that is used by package owners to be able to automatically receive packages and temporarily store packages safely. This tool uses an ESP-32Wroom microcontroller which will process input from the HC-SR04 ultrasonic sensor, HX-711 loadcell and Keypad. The courier can only open the box by inputting the code on the 4 x 4 keypad on the box. When the receipt is successfully entered, the door lock solenoid on the box will be ON and the box will open and the package will be stored in the box. After the package is put into the box by the courier, the package will move to another room below which can be closed automatically, and only the owner of the package box has access to open the box. Equipped with an ESP-32 Camera which can take pictures or photos of the package before putting it in the box. This device is integrated with Internet of Things technology where notifications about package status can be received and monitored in real-time remotely by the package recipient.